Patient and carer experience of hospital-based rehabilitation from intensive care to hospital discharge: mixed methods process evaluation of the RECOVER randomised clinical trial. Issue 8 (1st August 2016) - Ramsay, Pam; Huby, Guro; Merriweather, Judith; Salisbury, Lisa; Rattray, Janice; Griffith, David; Walsh, Timothy
Abstract : Objectives: To explore and compare patient/carer experiences of rehabilitation in the intervention and usual care arms of the RECOVER trial (ISRCTN09412438 ); a randomised controlled trial of a complex intervention of post-intensive care unit (ICU) acute hospital-based rehabilitation following critical illness. Design: Mixed methods process evaluation including comparison of patients' and carers' experience of usual care versus the complex intervention. We integrated and compared quantitative data from a patient experience questionnaire (PEQ) with qualitative data from focus groups with patients and carers. Setting: Two university-affiliated hospitals in Scotland. Participants: 240 patients discharged from ICU who required ≥48 hours of mechanical ventilation were randomised into the trial (120 per trial arm). Exclusion criteria comprised: primary neurologic diagnosis, palliative care, current/planned home ventilation and age <18 years. 182 patients completed the PEQ at 3 months postrandomisation. 22 participants (14 patients and 8 carers) took part in focus groups (2 per trial group) at >3 months postrandomisation. Interventions: A complex intervention of post-ICU acute hospital rehabilitation, comprising enhanced physiotherapy, nutritional care and information provision, case-managed by dedicated rehabilitation assistants (RAs) working within existing ward-based clinical teams, delivered between ICU discharge and hospital discharge. Comparator was usual care. Outcome measures: A novel PEQ capturing patient-reported aspects of quality care. Results: The PEQ revealed statistically significant between-group differences across 4 key intervention components: physiotherapy (p=0.039), nutritional care (p=0.038), case management (p=0.045) and information provision (p<0.001), suggesting greater patient satisfaction in the intervention group. Focus group data strongly supported and helped explain these findings. Specifically, case management by dedicated RAs facilitated greater access to physiotherapy, nutritional care and information that cut across disciplinary boundaries and staffing constraints. Patients highly valued its individualisation according to their needs, abilities and preferences. Conclusions: Case management by dedicated RAs improves patients' experiences of post-ICU hospital-based rehabilitation and increases perceived quality of care. Trial registration number: ISRCTN09412438.